The Effect of the CIRC Learning Model Using Flipbook Media on the Reading Comprehension Skills of Fourth-Grade Students at Madrasah Ibtidaiyah - Dwi Andika Saputra; Nurul Hidayah; Anton Tri Hasnanto (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2026)
This study was conducted in response to issues faced by students regarding the gap in reading proficiency between those who read fluently and those who still struggle, the limited use of interactive learning media and cooperative learning approaches, and the predominant reliance on conventional methods in face-to-face instruction. This study aims to determine the effect of the CIRC learning model assisted by flipbook media on the reading comprehension skills of fourth-grade students at MIMA 7 Labuan Ratu. This is a quantitative study using a quasi-experimental design. The study population consists of all 47 fourth-grade students. Class IVA, with 23 students, served as the experimental class implementing the learning model supported by flipbook media, while Class IVB, with 24 students, served as the control class implementing the SQ3R model. The sampling technique used was census sampling, employing multiple-choice questions to measure reading comprehension skills. The results of this study indicate that there is a significant effect of the CIRC learning model assisted by flipbook media on the reading comprehension skills of fourth-grade students at MIMA 7 Labuan Ratu. The results of the hypothesis test, normality test, and paired-sample t-test showed a significance value (two-tailed) of 0.000 < 0.05; therefore, H0 was rejected and H1 was accepted, indicating that the implementation of the CIRC learning model aided by flipbook media has an effect on the reading comprehension skills of fourth-grade students at MIMA 7 Labuan Ratu